Development and validation of the VISAGE AmpliSeq basic tool to predict appearance and ancestry from DNA. (September 2020) - Xavier, Catarina; de la Puente, Maria; Mosquera-Miguel, Ana; Freire-Aradas, Ana; Kalamara, Vivian; Vidaki, Athina; E. Gross, Theresa; Revoir, Andrew; Pośpiech, Ewelina; Kartasińska, Ewa; Spólnicka, Magdalena; Branicki, Wojciech; et al.
Highlights: We developed an MPS-based assay for simultaneous appearance and bio-geographical ancestry estimation. The assay underwent forensic validation through a collaborative exercise within the VISAGE Consortium. The assay proved to be robust and highly sensitive (down to100 pg for full profiles). MPS-based assays show low tolerance to common PCR inhibitors. Abstract: Forensic DNA phenotyping is gaining interest as the number of applications increases within the forensic genetics community. The possibility of providing investigative leads in addition to conventional DNA profiling for human identification provides new insights into otherwise "cold" police investigations. The ability of reporting on the bio-geographical ancestry (BGA), appearance characteristics and age based on DNA obtained from a crime scene sample of an unknown donor makes the exploration of such markers and the development of new methods meaningful for criminal investigations. The VISible Attributes through GEnomics (VISAGE) Consortium aims to disseminate and broaden the use of predictive markers and develop fully optimized and validated prototypes for forensic casework implementation. Here, the first VISAGE appearance and ancestry tool development, performance and validation is reported. A total of 153 SNPs (96.84 % assay conversion rate) were successfully incorporated into a single multiplex reaction using the AmpliSeq™ design pipeline, and applied for massively parallel sequencing with the Ion S5 platform. A collaborative effort involving six VISAGE laboratory partners was devised to perform all validation tests. An extensive validation plan was carefully organized to explore the assay's overall performance with optimum and low-input samples, as well as with challenging and casework mock samples. In addition, forensic validation studies such as concordance and mixture tests recurring to the Coriell sample set with known genotypes were performed. Finally, inhibitor tolerance and specificity were also evaluated. Results showed a robust, highly sensitive assay with good overall concordance between laboratories.